Honduran nursing care to pressure injuries in patients with invasive mechanical ventilation: A qualitative study - Bustamante, Yoselin Isabel Vallejo; Martinez, Oscar Fidel Antunez (Belitung Nursing Journal, 2025)
Background: Although substantial evidence exists regarding the treatment of pressure ulcers, there is a lack of studies demonstrating a comprehensive nursing approach for managing pressure ulcers in the ICU, particularly among patients with invasive mechanical ventilation from developing countries like Honduras. This gap in research is significant as the risk and impact of pressure ulcers on health recovery cannot be disregarded. Objective: This study aimed to analyze Honduran nursing care for pressure ulcers in patients with invasive mechanical ventilation admitted to Intensive Care Units. Methods: A qualitative study approach was used, with in-depth interviews conducted with 12 critical care nurses from July to September 2022. The interviews were recorded, and data analysis was performed using the participants’ narratives following Colaizzi’s steps. Results: Three themes were obtained, which provide insight into the phenomenon: “The strengths in Honduran nursing interventions,” “Negligence in the Honduran nursing care processes,” and “Vulnerabilities in the organizational structures.” Conclusion: Nurses’ experiences highlighted their timely reports and comprehensive, holistic care. However, they undergo negligence in their caring processes, such as low frequency of repositioning, lack of caring plans, and absence of self-training, leading to interdisciplinary work codependency for decision-making. Allocating resources toward nursing care and their professional growth is an investment in providing humane treatment and ensuring the prevention and management of pressure injuries in critical care patients. This study highlights the importance of comprehensive training and standardized protocols for intensive care nurses to improve pressure injury prevention and management in mechanically ventilated patients, emphasizing the need for regular patient repositioning, effective communication, and adequate resources to enhance patient care quality.